Literature Review: Hubungan Skor Modified Sequential Organ Failure Assessment (Msofa) dengan Nilai Diagnostik Prokalsitonin Pada Pasien Sepsis - Nurdiansyah, Nurdiansyah; Trisyani, Yanny; Mirwanti, Ristina (Universitas Malahayati, 2025)
ABSTRACT Sepsis is an organ dysfunction caused by infection and is one of the leading causes of mortality and morbidity worldwide. Early assessment of sepsis is essential to reduce mortality and morbidity rates. The modified Sequential Organ Failure Assessment (mSOFA) score and procalcitonin diagnostic values have been utilized as tools to evaluate organ dysfunction and as biomarkers in sepsis patients. This study aims to identify the relationship between mSOFA scores and procalcitonin diagnostic values in sepsis patients. This study was conducted by searching scientific articles in the PubMed, ScienceDirect, and Google Scholar databases using the keywords